Determinan Stunting Anak 6-24 Bulan di Kabupaten Timor Tengah Selatan Provinsi Nusa Tenggara Timur - Koro, Suriana; Hadju, Veni; As'ad, Suryani; Bahar, Baharuddin (Health Information : Jurnal Penelitian, 2018)
Nutritional problems in children under five are still a public health problem if the prevalence of stunting is> 20%. The prevalence of stunting in general in the world is also a public health problem because it is still 26%. Nationally, the prevalence of stunting in children under five in Indonesia is 37.2%. This means that the problem of nutrition in Indonesia is still a serious public health problem. Meanwhile, the proportion of children under five with stunting is 48.2% in NTT Province, including a critical public health problem. Based on this background, this study aims to determine the determinants of stunting of children 6-24 months in South Central Timor District, East Nusa Tenggara Province. B This research is an observational study with a cross-sectional design. The research was carried out in nine sub-districts of Timor Tengah Selatan Regency. Baduta food consumption data were obtained through consumption recall, while other data were obtained through questionnaires by enumerators. Analysis of nutrients in food using a food processor 2 (FP2). The statistical test used is Chi-Square. The number of respondents studied was 3480 children, with stunting and severe stunting as many as 1416 children (40.7%), most of whom were boys, as many as 1870 children (53.7%), for 12-24 months there were 1916 children, (1%), where the results of the chi square test are significant p <0.05. Education of mothers and fathers, respectively 1827 people (52.5%) and 1754 people (50.4%) with basic education did not complete and graduated from junior high school, with the majority of jobs being mother farmers (83.3%) and fathers (65.0%), most of the socio-economic conditions are low (83.5%). Maternal TB was significant (p = 0.000) as well as parity and birth spacing, the results of the chi-square test were significantly significant, p <0.005, while exclusive breastfeeding was only 596 people (17.1%). Nutritional needs did not reach the Recommended dietary allowance. (RDA) <80% RDA, energy intake (90.3%), protein (82.6%), fat (97.9%) and KH (82.0%). History of diarrhea (17.4%), fever (32.6%), shortness of breath (2.3%), cough (31.0%) and runny nose (29.2%) and the results of the chi-square test were only fever. Significant with p = 0.016. The logistic regression results showed that gender and maternal height were the most associated with stunting nutritional status. The determinant factors of stunting were the child's age, sex, mother's education, maternal occupation, mother's height, parity, birth spacing, protein intake and a history of fever.